Monitoring invasive macroalgae in southern Portugal: drivers and citizen science contribution - Herrero, Javier Jiménez; Simes, Dina Costa; Abecasis, Rita; Relvas, Paulo; Garel, Erwan; Ventura Martins, Paula; Santos, Rui (Frontiers in Environmental Science, 2023)
Under certain environmental and oceanographic conditions, macroalgae can overgrow and accumulate in massive quantities on beaches, causing serious ecological and economic impacts. To address this problem, a citizen science monitoring platform was created to determine the spatial and temporal distribution of macroalgae accumulations along the beaches of Algarve in southern Portugal, with the aim to assess the extent of beach-cast events and their relationship with abiotic factors. A Redundancy Analysis (RDA) and a permutational analysis of variance (PERMANOVA) were carried out to explore the relationship between macroalgae accumulation level and the abiotic variables: sea surface temperature, wind speed, wind direction, currents, maximum sea level, significant wave height, salinity, nitrate, ammonium, phosphate, precipitation and radiation. The citizen science campaign showed great participation, resulting in 404 submissions between July 2021 and September 2023. The campaign revealed that three species of macroalgae accumulated on the beaches of Algarve, Ulva sp. (with the presence of Ectocarpales and Dyctiotales) along the sandy eastern coast, and the invasive species Asparagopsis armata and Rugulopteryx okamurae in the rocky central and western beaches, respectively. The accumulations of R. okamurae increased from 2021 to 2023, were registered throughout the year and were more abundant than those of Ulva sp. and A. armata, which were only observed in spring and summer. The highest levels of R. okamurae beachcast depositions were related to strong wave conditions, and high sea surface temperature and salinity. The accumulation of Ulva sp. was related to high sea surface temperature and salinity whereas A. armata was also correlated with winds parallel to the shore (NW-W). PERMANOVA analysis revealed that sea surface temperature and wave conditions had a significant effect on the overall abundance of macroalgae beach-cast accumulations. Overall, our citizen science campaign effectively involved the public, leading to the collection of important data on monitoring macroalgae accumulations. Through these findings, we were able to pinpoint the environmental, atmospheric, and hydrodynamic factors that contribute to their development, movement, and buildup along the Algarve coastlines